2012
DOI: 10.1007/978-3-642-30726-3_18
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Differences in Type 2 Diabetes Mellitus and Dyslipidemia Therapy: PPAR Agonists

Abstract: The influence of sex on the development of obesity, Type 2 Diabetes Mellitus (T2DM), and dyslipidemia is well documented, although the molecular mechanism underlying those differences reminds elusive. Ligands of peroxisome proliferator-activated receptors (PPARs) are used as oral antidiabetics (PPARgamma agonists: thiazolidinediones, TZDs), or for the treatment of dyslipidemia and cardiovascular diseases, due to their lipid-lowering properties (PPARalpha agonists: fibrates), as PPARs control transcription of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 128 publications
1
26
0
2
Order By: Relevance
“…The concomitant increase in PPAR target genes involved in lipid synthesis (FAS) or transport (FAT) in lungs of female fetuses of diabetic rats fed the 6% olive-oil-or the 6% safflower-oil-supplemented diets indicates that this increase may contribute to the accumulation of triglycerides and to providing lipid substrates needed for the production of surfactant lipids in these experimental groups (Rehan & Torday 2012). The sex differences observed can be explained by the complex effects of estrogens, which induce profound changes in lipid metabolic pathways and regulate PPARs expression, and of androgens, which induce changes in the expression of multiple genes, including several PPAR coactivators and corepressors (Bresson et al 2010, Benz et al 2012, Oosthuyse & Bosch 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concomitant increase in PPAR target genes involved in lipid synthesis (FAS) or transport (FAT) in lungs of female fetuses of diabetic rats fed the 6% olive-oil-or the 6% safflower-oil-supplemented diets indicates that this increase may contribute to the accumulation of triglycerides and to providing lipid substrates needed for the production of surfactant lipids in these experimental groups (Rehan & Torday 2012). The sex differences observed can be explained by the complex effects of estrogens, which induce profound changes in lipid metabolic pathways and regulate PPARs expression, and of androgens, which induce changes in the expression of multiple genes, including several PPAR coactivators and corepressors (Bresson et al 2010, Benz et al 2012, Oosthuyse & Bosch 2012.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence of diabetes-induced changes in lipid metabolism, sex-dependent changes in lipid metabolic pathways, and of the role of estrogens in lipid metabolism (Kautzky-Willer & Handisurya 2009, Benz et al 2012, Oosthuyse & Bosch 2012. Also estrogen-responsive elements are found in PPARs promoters, and estrogens can regulate PPARs expression and activation (Yoon 2009, Oosthuyse & Bosch 2012.…”
Section: Discussionmentioning
confidence: 99%
“…TZDs are PPARγ agonists; insulin-sensitizing drugs used in the treatment of T2D 93. Although some studies have suggested that TZDs may be more effective in women compared with men,9496 the majority of larger studies have not reported sex-specific differences 93.…”
Section: Glucose-lowering Therapymentioning
confidence: 99%
“…Both, pioglitazone and rosiglitazone, increase the risk of heart failure with high strength of evidence (SOE), and also oedema (high SOE) and fractures in women (moderate SOE) (Habib et al 2010;Jonas et al 2011) (see also Benz et al 2012).…”
Section: Glitazonesmentioning
confidence: 95%